Influencia del uso de brix 3000 vs sistema rotativo en el sellado marginal de restauraciones directas in vitro - Vivanco Ludeña, Dennisse Dayana (2019)
The purpose of this study is to determine the influence of the use of BRIX 3000 versus the rotary system on the marginal sealing of in vitro direct restorations. Thirty-three recently extracted human premolars were selected, with caries on the occlusal and proximal surface; where carious tissue removal was performed, for which it was worked with two groups of 15 pieces each, in group A: by means mechanical chemical technique with BRIX 3000 gel is used and in group B: by conventional technique, using rotary system. All dental pieces were restored by applying a glass ionomer base, adhesive system, and composite resin. The specimens were subjected to thermal cycles at temperatures of 5° to 55°C (+ or - 2°C), in a total of 300 cycles, each a quarter was 15 seconds; then the waterproofing of the apices was done by applying composite resin and double layer of transparent nail varnish except for 2mm around the restoration, then they were immersed in 0.5% methylene blue for 72 hours at 37°C. Subsequently, the samples were cut mesiodistal through the restoration for observation in the stereomicroscope. The results showed that there was a better marginal seal in the rotating system group with 68.33%, compared to the BRIX 3000 group with 21.67%; establishing that, there is a significant statistical difference in both techniques in the marginal seal (p = 0.000); In addition with the use of the rotary system, a better marginal sealing in occlusal was obtained with 90.00% (p = 0.000) and in the gingival margin, 46.67% did not present marginal filtration (p = 0.032); which indicates that there is significant statistical difference in the use of both techniques, at the level of the occlusal and gingival margin in the marginal sealing of direct restorations. Keywords: dental caries, enzymatic gel, microfiltration, thermocycling.